International tourists' willingness to use cryptocurrency for payments in Prague - Shafikova, Karina (2024)
This bachelor thesis explores international tourists' willingness to use cryptocurrency for payments in Prague. It examines the integration of cryptocurrencies in tourism, highlighting their benefits like security, efficiency, reduced transaction costs, and challenges such as volatility, regulatory uncertainties, and limited acceptance. Using surveys and case studies, the research reveals that while awareness of major cryptocurrencies like Bitcoin and Ethereum is high, actual usage among tourists is low due to security concerns and limited business acceptance. The study emphasises the need for regulatory clarity, improved infrastructure, public education, and strategic partnerships to foster cryptocurrency adoption in Prague's tourism sector. The findings contribute to understanding how cryptocurrencies can enhance the tourism industry, offering recommendations for policymakers and businesses to promote wider acceptance of digital currencies and positioning Prague as a tech-forward destination.